PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN SEKS BEBAS REMAJA DI BPRSW YOGYAKARTA - Chanif Kurnia Sari; Iis Dahlia (Jurnal Delima Harapan, 2021)
Free sex is sexual behavior by individuals before marriage which is common in adolescence. As a result of changes in adolescent sexual attitudes and behavior will increase adolescent sexual problems. The consequences that can occur from free sex are unprotected sexuality, venereal disease, mortality of young mothers and their babies, abortion and unwanted pregnancy. The incidence of childbirth as many as 219 occurred in Sleman in 2017 and there were 47 marriage dispensation agreements in 2018. Factors of knowledge about reproductive health are important factors that must be possessed by adolescents to prevent the occurrence of free sex. This study aims to determine the effect of reproductive health education on adolescent free sex knowledge. This study uses a type of pre experiment design with a one-group pretest-posttest design. The population in this study were teenagers in BPRSW as many as 30 people, with sampling using total sampling. Data collection techniques using the method of observation and questionnaires. Test validity in this study using product moment correlation and declared valid with the value of r count <r table (0.05). Reliability test using Cronbach's alpha obtained Cronbach's alpha value of 0.745 so it was declared reliable. Data analysis uses univariate and bivariate analysis. Bivariate analysis using paired T-test. The results of the study indicate that reproductive health education influences adolescent knowledge in BPRSW Yogyakarta, with a value of p = (0.048) <α (0.05). As many as 24 (80.0%) of respondents had good category knowledge after being given health education about free sex.